2000
DOI: 10.1029/1999jd900454
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aerosol optical depth inferred from surface measurements with that determined by Sun photometry for cloud‐free conditions at a continental U.S. site

Abstract: Abstract. Evaluation of the forcing of climate by aerosol scattering of shortwave radiation in cloud-free conditions (direct aerosol forcing) requires knowledge of aerosol optical properties on relevant spatial and temporal scales. It is convenient to measure these properties at the surface. However, before these measurements can be used to quantitatively estimate direct climate forcing, it is necessary to determine the extent to which these properties are representative of the entire atmospheric column. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 30 publications
8
38
1
1
Order By: Relevance
“…The variations of water vapor could lead to the swelling or condensation of particles, and consequently the change of the microstructure and composition of the particles, which affects the relationship between AOT and PM. Vertical profile of aerosols could also introduce errors in the relationship, because of the significant contribution of aerosols above the boundary layer to extinction, especially when weak atmospheric convection happens [48]. Therefore, information on the aerosol vertical profiles from ground-based lidars and space-borne lidars, such as the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO), could be applied into the retrieval of PM from satellite data.…”
Section: Discussionmentioning
confidence: 99%
“…The variations of water vapor could lead to the swelling or condensation of particles, and consequently the change of the microstructure and composition of the particles, which affects the relationship between AOT and PM. Vertical profile of aerosols could also introduce errors in the relationship, because of the significant contribution of aerosols above the boundary layer to extinction, especially when weak atmospheric convection happens [48]. Therefore, information on the aerosol vertical profiles from ground-based lidars and space-borne lidars, such as the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO), could be applied into the retrieval of PM from satellite data.…”
Section: Discussionmentioning
confidence: 99%
“…However they did find at their site that the fraction of small particles was larger near the surface relative to higher altitudes. Bergin et al (2000) concluded that attempts to predict column AOD from surface measurements, both with and without associated lidar measurements, underestimated the measured column AOD by between 30 and 70 %. Slater and Dibb (2004) found, in rural New England, that there was only a moderate correlation of surface and column aerosol properties.…”
Section: R P Aryal Et Al: Comparison Of Surface and Column Measurementioning
confidence: 99%
“…These measurements are often assumed to be representative of the overlying aerosol column, or at least of the aerosol boundary layer. Several experiments have been conducted to characterize the connection between surface and column aerosol properties (Bergin et al, 2000;Andrews et al, 2004;Slater and Dibb, 2004;Sheridan et al, 2012;Quinn et al, 2004). Most of these experiments were at continental locations including Oklahoma (Bergin et al, 2000;Andrews et al, 2004), rural New England (Slater and Dibb, 2004), central Illinois (Sheridan et al, 2012), and Big Bend, Texas (Hand et al, 2004).…”
Section: R P Aryal Et Al: Comparison Of Surface and Column Measurementioning
confidence: 99%
“…SAE represents the wavelength dependence of scattering and varies inversely with particle size, so that small values of SAE indicate larger aerosol particles (e.g., dust and sea salt), and large values of SAE indicate relatively smaller aerosol particles (Schuster et al, 2006;Bergin et al, 2000, and references therein). AAE represents the wavelength dependence of absorption and depends on the composition of absorbing aerosols, such that aerosol materials have a unique range of AAE values Bergstrom et al, 2002Bergstrom et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%